Left atrial contractile strain predicts recurrence of atrial tachyarrhythmia after catheter ablation. (1st July 2022) - Nielsen, Anne Bjerg; Skaarup, Kristoffer Grundtvig; Djernæs, Kasper; Hauser, Raphael; San José Estépar, Raúl; Sørensen, Samuel Kiil; Ruwald, Martin Huth; Hansen, Morten Lock; Worck, René Husted; Johannessen, Arne; Hansen, Jim; Biering-Sørensen, Tor
Abstract: Background: Despite improvement in treatment strategies of atrial fibrillation (AF), a considerable number of patients still experience recurrence of atrial tachyarrhythmia (ATA) following catheter ablation (CA). This study aimed to investigate the prognostic value of left atrial (LA) deformation analysis in a large group of patients undergoing CA for AF. Methods: This study included 678 patients with AF. Echocardiography including two-dimensional speckle tracking echocardiography (2DSTE) was performed in all patients prior to CA. Logistic regression analysis was used to assess the association between ATA recurrence and LA strain during reservoir phase (LASr), LA strain during contraction phase (LASct), and LA strain during conduit phase (LAScd). Results: During one-year follow-up, 274 (40%) experienced ATA recurrence. Median age of the included study population was 63.2 years (IQR: 55.5, 69.5) and 485 (72%) were male. Patients with recurrence had lower LASr (22.6% vs. 25.1%, p = 0.001) and LASct (10.7% vs. 12.4%, p < 0.001). No difference in LAScd was observed. After adjusting for potential clinical and echocardiographic confounders LASr (OR = 1.04, CI95% [1.01; 1.07], p = 0.015, per 1% decrease) and LASct (OR = 1.06, CI95% [1.02; 1.11], p = 0.007, per 1% decrease) remained independent predictors of recurrence. However, in patients with a normal-sized LA (LA volume index<34 mL/m 2 ), only LASct remained an independent predictor of recurrence (OR = 1.07, CI95% [1.01; 1.12], p = 0.012, per 1% decrease). Conclusion: In patients undergoing CA for AF, LA deformation analysis by 2DSTE could be of use in risk stratification in clinical practice regarding ATA recurrence, even in patients with a normal-sized LA. Highlights: LA strain by 2DSTE may predict recurrence of atrial tachyarrhythmia after catheter ablation for AF. LA contractile strain may predict recurrence even in patients with normal-sized LA. LA strain could be useful in clinical practice to help identify high-risk patients and make a personalised treatment plan. The present findings promote the current understanding of the pathophysiology of the LA in patients with AF.